Faktor-faktor yang Mempengaruhi Kunjungan Pasien Terhadap Standar Pelayanan di Apotek Kimia Farma 278 Versailles dengan Menggunakan Analisis Faktor - Il madi; Besse Arnawisuda Ningsi (Program Studi Statistika FMIPA UNJ, 2018)
To guarantee pharmaceutical service standards (Apotek), factors that need to be considered are the quality of human resources, complete facilities and infrastructure, prescription services (including drug information), counseling, monitoring drug use, health education and promotion, and evaluation of treatment. This is very important because it will have a positive impact and is very profitable, if the standard is met. Kimia Farma 278 Versailles pharmacies need to improve quality, especially in terms of service. Factor analysis methods can be used to see what factors influence patient visits to service standards. This type of research is descriptive research. Based on the results of the analysis there are 5 factors that are formed from the process of reducing delivery and Go-Mart services that can help patients. It is important to attract interest in coming to the pharmacy. Offered discounts, medicines submitted with standardized health education, offering drug packaging is more economical, the drug offered as a substitute does not have a negative impact, the ability of the knowledge officer to offer substitute drugs in accordance with the Service Standards at the pharmacy, Treatment is more maximal with the presence of checks from the officer (F1). Prices are commensurate with the drugs that are expected, quality drugs, pharmacies have a good reputation (F2). Clean, neat and comfortable, the price is commensurate with the drug you expect (F3). Having decent and adequate building facilities and interior, building exterios look good (F4), and the suitability of the product you want (F5)